2022
DOI: 10.1002/aenm.202103383
|View full text |Cite
|
Sign up to set email alerts
|

Operando Monitoring and Deciphering the Structural Evolution in Oxygen Evolution Electrocatalysis

Abstract: The oxygen evolution reaction (OER) acts as the bottleneck of some crucial energy conversion and storage technologies involving water electrolysis, CO2 electrolysis, and metal‐air batteries, among others. The challenging sluggish reaction kinetics of the OER can be overcome via developing highly efficient electrocatalysts, which experience a dynamic structural evolution process during the reaction. However, the reaction mechanism of the structural transformation of electrocatalysts during the OER and the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
98
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(98 citation statements)
references
References 105 publications
0
98
0
Order By: Relevance
“…S40A) and ~597 cm −1 (fig. S40D) are associated with the formation of CoOOH species, which indicates that LSCO-0.05-0h and LSCO-0.625-6h are working with LOM ( 36 38 ), while the unchanged spectra of LSCO-0.05-6h and LSCO-0.625-0h indicate the AEM mechanisms. Despite the fact that LOM is coupled with amorphization or surface reconstruction, this amorphization process is the dynamic structural evolution of the material in the catalytic process under the application of OER voltage.…”
Section: Resultsmentioning
confidence: 99%
“…S40A) and ~597 cm −1 (fig. S40D) are associated with the formation of CoOOH species, which indicates that LSCO-0.05-0h and LSCO-0.625-6h are working with LOM ( 36 38 ), while the unchanged spectra of LSCO-0.05-6h and LSCO-0.625-0h indicate the AEM mechanisms. Despite the fact that LOM is coupled with amorphization or surface reconstruction, this amorphization process is the dynamic structural evolution of the material in the catalytic process under the application of OER voltage.…”
Section: Resultsmentioning
confidence: 99%
“…This viewpoint is further demonstrated by electrochemical impedance spectroscopy (FigureS13). Lower charge-transfer resistance for CdS@Ni has been confirmed by the evidence that a smaller arch is detected [53][54][55][56]. Photo-irradiation can further decrease the arc diameter, suggesting that the isolated Ni atoms act as electron collectors to facilitate the separation of photogenerated electron-hole pairs on the CdS@Ni interface.…”
mentioning
confidence: 78%
“…The application of infrared spectroscopies in chemistry can be divided into two aspects: basic research of molecular structure and analysis of chemical composition. [116] Infrared spectroscopy can be used to infer the unknown structure according to the position and shape of the absorption peak in the spectrum, and determine the content of each component in the mixture according to the intensity of the characteristic absorption peak. [117] In-situ Infrared is used to directly conduct infrared analysis of the product during reaction, and test the changes in the structure of functional groups, which can better simulate the experimental process and is very helpful to explain the reaction mechanism (Figure 8a).…”
Section: In-situ Infrared Spectroscopymentioning
confidence: 99%
“…Infrared spectroscopy provides fingerprinting of polarized free radicals for key oxygen intermediates involved in OER and is concentrated within a window of 800-1600 cm À 1 . [116][117][118] Liu et al [119] reported an amino-rich layered network carbon (amino-HNC) loaded on carbon paper, and by using in situ infrared spectroscopy, in the OER process in the acid medium, the key structural evolution of H 2 NÀ (*OÀ C)À C formed by adsorption of *O intermediates on the active H 2 NÀ C=C moiety was observed (Figure 8b). Furthermore, they reported a lattice strain NiFe-MOF as an OER electrocatalyst.…”
Section: In-situ Infrared Spectroscopymentioning
confidence: 99%